Statistical properties of solar energetic proton events - Paassilta, Miikka (fi=Turun yliopisto|en=University of Turku|, 2023)
The Sun is the source of several different kinds of high-energy particles that are most prominently released in sudden large eruptions, known as solar energetic particle events. These particles, which escape the Sun and are accelerated in the coronal plasma, contribute substantially to the radiation environment in near-Earth and interplanetary space and therefore constitute an important consideration in mitigating the risks of space missions and other space-related human activities. Although the basic mechanisms related to energetic particle release and acceleration are fairly well known in principle, electrically charged particles are subjected to multiple complicated physical processes between their point of origin and an observer in interplanetary space. This fact, together with the changing conditions at the particle source, causes the observed particle event characteristics to vary a great deal, seriously complicating any attempt to understand, model, and predict their fluxes in near-Earth space. In the work forming the basis for this dissertation, we examined three large selections of solar energetic particle events through various statistical methods. Relying on data mainly collected by spacecraft, we identified particle events that fulfilled certain criteria, determined their likely association with other solar phenomena (such as solar flares and coronal mass ejections), and characterised the events by calculating estimates for their intensity rise times, the differences between the particle injection times derived using different methods, the magnetic connectivity between the particle source and the observer, and various other quantities. These observables were studied for statistically significant dependencies in order to uncover information about particle release and transport. The event listing compiled for the first of the three articles included herein was additionally made available as an electronic online catalogue that has been thereafter regularly updated by the author. We found that the features of solar energetic particle events do not exhibit any general, straightforward dependence on the longitudinal distance or the magnetic connectivity between the particle source and the observer, especially in their initial phase. The studied event populations appear highly variable in this respect, and they might include several different classes of events that are not readily distinguishable based on the available information. However, the intensity rise times, the delays between the event-related X-ray flare and the modelled event onset, as well as the relative durations of events, would seem to be at least somewhat dependent on the magnetic connectivity and the iron abundance of the event: a strong modelled magnetic connection and iron-rich composition tend to imply a proton event that rises more quickly and lasts for a shorter period of time than does an event with the opposite characteristics. The longitudinal spread of energetic particles in large events is not strongly dependent on particle energy, but might depend on the general solar cycle-specific conditions in interplanetary space. Overall, our results underscore the desirability of combining good observational statistics with reasonably comprehensive numerical modelling of particle transport effects in efforts to gain a better understanding of the processes involved in solar particle events and to develop applications for predicting these events.